Synthesis and Evaluation of Anisomelic acid-like Compounds for the Treatment of HPV-Mediated Carcinomas - Rajendran Senthilkumar; Yury Brusentsev; Preethy Paul; Parthiban Marimuthu; Fang Cheng; Patrik C. Eklund1; John Elias Eriksson (NATURE PUBLISHING GROUP, 2022)
The vast majority of cervical and 75% of oropharyngeal carcinomas are triggered by infection with a type of high-risk oncogenic human papillomavirus (HPV). It is well-known that E6 and E7 oncoproteins are critical for viral-induced cancer, and hence, they represent valuable targets for therapeutic intervention in HPV-mediated cancers. Our earlier research on the cembranoid, anisomelic acid (AA) showed that, AA has the potential to induce apoptosis in HPV cells by the depletion of E6 and E7 oncoproteins. The present study describes the structure-activity relationship and the evaluation of synthetic AA like compounds, i.e simplified cembranoid-like structures, as HPV inhibitors against some papilloma cell lines. Both from experimental and computational results, we observed that these compounds induced apoptosis by the same E6/E7-based mechanism as AA, but at earlier time points, thus being far more effective than AA. Further, the data indicated that only part of the structure of AA is required for the molecular action. Based on these results, we identified some novel and potential compounds for specific treatment of HPV-associated carcinomas.